The relationship of the process of reading in EGP with the process of reading in ESP and the product of reading in EGP and ESP - Talebi, Seyed Hassan; Abbasabadi, Mahmoud Moradi (Penerbit UKM, 2015)
This study using ex post facto design had two purposes. First, it attempted to fi nd out if there was any relationship between the process of reading in EGP (English for General Purposes) and ESP (English for Specicfi c Purposes). Second, it intended to investigate if the EGP reading process would correlates with the EGP and ESP reading product. Thirty nine Iranian tertiary level students received reading comprehension tests as well as reading strategy questionnaires in EGP and ESP. Based on the mean score of the EGP reading strategy questionnaire the participants were classifi ed into two groups of low and high awareness and use of reading strategies. Analysis of data using one-way ANOVA and multivariate analysis of variance evinced the high group had more awareness and use of strategies in ESP and outperformed the low group in ESP reading comprehension test. However, no signifi cant difference was found in EGP reading comprehension test between the two groups. It was concluded that awareness and use of strategies in EGP coupled with content knowledge would be a good predictor of a successful academic reading performance. EGP teachers would be able to improve the strategic reading competence of students to be transferred to ESP reading tasks. ESP practitioners would be able to do needs analysis for content reading courses so that possible defi ciencies in strategic competence would not result in ineffi ciency in ESP reading.